Age and gender differences in kinematics of powerful instep kicks in soccer - Katis, A.; Kellis, E.; Lees, A. (Sports Biomechanics, 2015)
Soccer kicking training should be adjusted to the characteristics of the athletes. Therefore, examination of differences in kicking kinematics of females and pubertal players relative to males is worthwhile. The purpose of the study was to compare kicking kinematics and segmental sequence parameters between male, female, and pubertal players. Ten adult male, ten adult female, and ten male pubertal players participated in the study. Participants performed five consecutive kicking trials of a stationary ball, as powerful as they could. Analysis of variance showed significantly higher ball velocity, higher joint linear velocities for the knee and the hip, and higher angular velocities of the knee and the ankle for males compared to female and pubertal players (p < 0.05). Similarly, the peak joint velocity was achieved significantly closer to ball impact in males compared to other groups (p < 0.05). Males also showed a more plantarflexed ankle immediately before ball impact (p < 0.05). Females and pubertal players may benefit from skill training aiming to increase ankle plantarflexion and hip flexion prior to ball impact, and to adjust thigh and shank motion, such that the shank-foot segment travels through a higher range of motion and with a greater velocity.